(untitled) (Journal of the Bangladesh Chemical Society, 2013)
This paper describes the preparation and characterization of mixed ligand complexes of Co(II) and Fe(III) ions with maleic acid and heterocyclic amines of general formula [M(ME)L] and K[M(ME)L] (where M = Co(II) (1-4), Fe(III) (5-6); ME = C4H2O4 (1-4), 2C4H2O4 (5-6); L = C5H6N2 (1), C9H7N (2-3), C9H6NO (4), C5H5N.H2O (5), C6H7N (6)). The molecular structures of the complexes have been determined by spectral, magnetic studies and elemental analysis. Journal of Bangladesh Chemical Society, Vol. 25(2), 139-145, 2012 DOI: http://dx.doi.org/10.3329/jbcs.v25i2.15066